Reversão sexual de tilápias gift criadas em hapas e submetidas a diferentes taxas de alimentação em alta frequência - Santos, Anderson Aparecido Dias [UNESP] (2015)
This study was conducted in the first fortnight of April 2013 in order to evaluate different feed rates for high frequency power continues (day and night) in the sex reversal of tilapia larvae newly hatched GIFT strain, fed with commercial feed with 30 mg of 17-α-methyltestosterone / kg-1. The experimental design was completely randomized with three treatments, a control group and four replications. The treatments consisted of three power rates which are: upper, middle and lower. In the first week the rates were 250, 200 and 150% of the biomass for each treatment and the second week these figures were reduced to 200, 150 and 100% respectively, the control group received 185% of body weight in feed without adding hormone throughout the period. The larvae with initial weight of 0.021 ± 0.01 g were distributed in the density of 1,000 larvae per hapa of 343 liters. The ration was provided by automatic feeders 30 in 30 minutes according to the treatment and adjusted daily for Programmable Logic Controller (PLC). The results of sex reversal did not differ among themselves within the processed than in the control group differed from all others. The percentages of males to the seven days were 94.6, 97.6 and 96.6% for the top treatments, middle and bottom respectively. The automation of feeding is an alternative for decreasing the amount of hormone dispensed, since reducing the reversal period for seven days due to the high frequency power continues (day and night) prevents the supply of feed hormone with from seven to 14 days and may be a possible replacement for the conventional technique practiced in commercial fish farms